PENGARUH REWARD, PUNISHMENT, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BIMA MULTI FINANCE CABANG BATAM - Ferry Muliadi Manalu (Universitas Riau Kepulauan, 2020)
The purpose of reward, punishment, and motivation of work to simultaneously and partially on the performance employees of PT. Bima Multi Finance Batam branch. This type of research is quantitative research. The population and sample this study were all employees of PT. Bima Multi Finance Batam branch, totaling 35 employees.The results of reward, punishment and work motivation variables have a significant effect on employee performance, on simultaneous test results with sig (0.001) α (0.05) and Fcount Ftable (7.036 2.901). Partial test results reward variable has a significant positive effect on employee performance with a significance value α (0.008 0.05) and tcount 2.846 t table 2.040. Partial test results of the punishment variable have significant negative effect on employee performance with a significance value α (0.001 0.05) and t -3.699 t table 2.040. Results partial of work motivation have a significant positive effect on employee performance with a significance value α (0.015 0.05) and tcount 2.579 t table 2.040.